2016
DOI: 10.1016/j.jad.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Categorical and dimensional psychopathology in Dutch and US offspring of parents with bipolar disorder: A preliminary cross-national comparison

Abstract: Objective Accumulating evidence suggests cross-national differences in adults with bipolar disorder (BD), but also in the susceptibility of their offspring (bipolar offspring). This study aims to explore and clarify cross-national variation in the prevalence of categorical and dimensional psychopathology between bipolar offspring in the US and The Netherlands. Methods We compared levels of psychopathology in offspring of the Pittsburgh Bipolar Offspring Study (n=224) and the Dutch Bipolar Offspring Study (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…However, cross‐national variation is an issue with BD‐NOS, as studies show more variation when BD‐NOS is included as a result of different methods, interpretation of criteria, and prevalence rates across countries. This was also the case in our study comparing categorical and dimensional psychopathology from the Pittsburg BIOS study and the Dutch Bipolar Offspring Study (Mesman et al., ). BD‐NOS prevalence rate in the Pittsburgh sample was high (6.7%), but was not assessed in Dutch offspring because of unclear criteria and could therefore not be compared directly.…”
supporting
confidence: 76%
“…However, cross‐national variation is an issue with BD‐NOS, as studies show more variation when BD‐NOS is included as a result of different methods, interpretation of criteria, and prevalence rates across countries. This was also the case in our study comparing categorical and dimensional psychopathology from the Pittsburg BIOS study and the Dutch Bipolar Offspring Study (Mesman et al., ). BD‐NOS prevalence rate in the Pittsburgh sample was high (6.7%), but was not assessed in Dutch offspring because of unclear criteria and could therefore not be compared directly.…”
supporting
confidence: 76%
“…50 Both projects used the Achenbach Child Behavior Checklist (CBCL) 51 as well as similar semi-structured interviews (eg, the Kiddie Schedule for Affective Disorders and Schizophrenia). 52 After controlling for age, rates of DSM-IV BD-I (2.2% in the US sample and 1.5% in the Dutch sample) and BD-II (2% and 1%, respectively) were similar.…”
Section: | International Findingsmentioning
confidence: 99%
“…Translating scales into multiple languages and pursuing cross-cultural validation are accelerating progress by using consistent definitions, 50 revealing considerable continuity in phenomenology. 53 Combining data sets internationally would help calibrate definitions and examine common risk factors.…”
Section: | International Findingsmentioning
confidence: 99%
“…Other studies have found childhood-onset of BPD to be associated with other pernicious outcomes including increased irritability, mood lability, worse severity and course of illness, psychotic symptoms, worse response to lithium and increased risk for comorbid diagnoses and suicidality25 (w12–14). Studies comparing the USA to European countries demonstrate an earlier age of onset among US samples than European samples12 (w15). Reasons for differing ages of onset are yet unclear.…”
Section: Phenomenologymentioning
confidence: 99%